Epidemiology and patient characteristics of the US myasthenia gravis population: real-world evidence from a large insurance claims database - Richard J Nowak; Lesley-Ann Miller-Wilson; Joel Arackal; Yuriy Edwards; Jennifer Schwinn; Kristen Elizabeth Rockstein; Brett Venker (BMJ Neurology Open)
Background The epidemiology of myasthenia gravis (MG), a rare autoimmune disease, is not completely understood. This retrospective claims analysis assessed the epidemiologic rates of MG in the USA and the characteristics of the incident and prevalent MG populations.Methods Patients with MG were identified using Inovalon closed claims data; those with ≥2 International Classification of Diseases, 10th Revision (ICD-10) codes for MG from 2016 to 2019, separated by ≥30 days, were eligible. Patients in the prevalent cohort had continuous insurance coverage from January to December 2019. Patients in the incident cohort had continuous insurance coverage from January 2018 to December 2019 and no MG claims before 2019. Incidence and prevalence rates were adjusted using US census data. Treatment utilisation was assessed in both cohorts and grouped by provider type. Exacerbations were identified using ICD-10 code G70.01; codes occurring ≤30 days following a previous exacerbation code were considered as part of a single event.Results The incident cohort included 1442 patients (adjusted incidence: 4.3 per 100000); the prevalent cohort included 14 373 patients (adjusted prevalence: 35.7 per 100 000). In 2019, approximately two-thirds of patients in both cohorts (incident, 67.7%; prevalent, 61.6%) received MG treatments, most commonly acetylcholinesterase inhibitors, followed by oral steroids. Among incident patients with ≥1 year of continuous follow-up (n=1204), 32.1% (n=387) experienced ≥1 exacerbation, with 50% (n=194) having ≥2 exacerbations and 41% (n=159) having an exacerbation as the index MG event.Conclusions Estimates of MG incidence and prevalence were comparable to findings from two recent US studies. Acetylcholinesterase inhibitors and corticosteroids remain widely used. Exacerbations occurred in >30% of incident patients with ≥1 year of continuous follow-up, including 13% who had a relapse as their index event. These results highlight the need for earlier detection and use of more effective therapies in the treatment paradigm to achieve sustained disease control.